Analisis Usahatani Jagung( Zea Mays) di Desa Dosroha Kecamatan Simanindo Kabupaten Samosir Provinsi Sumatera Utara - Perkasa Sidabutar; Yusmini '; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Corn is the second food comodity after rice and a source of calories or food instead of rice. Demand of corn will be increased every year, so it is necessarry to increase rate of production. Focus of this study is to determine the net income, corn farming efficiency of corn farmers, families income, and to find out the related issues. This research was conducted in the Dosroha village, Simanindo district, Samosir regency, North Sumatera. Take about three months from August-October 2013. This study was performed by using census method,where respondents are 26 active corn  farmers Dosroha village. Survey results showed that the average of corn production is 5,688 kg/ha/cropping season with an average of selling price is Rp 2,062/kg. The average of gross income is Rp 8,091,538/land area/cropping season or Rp 11,726,867/ha/cropping season. The average of net income received by farmers was Rp 2,992,925/cultivation area/cropping season or Rp 4,334,653/ha/cropping season. The average of families income is Rp 3,474,005/land area or Rp 5,031.87/ha/cropping season with an average of land area is 0.69 ha. Based on  the efficiency analysis, efficiency of corn farmers in Dosroha village is 1.57,  means that for every Rp 100 of expense farmers will make a profit is Rp 0.57, so we can say that the corn farmer in Dosroha village already efficient in RCR term. Keywords: Produce mize, Income, profit, farming